Nacionalna identifikacija v Kanadi - Potocco, Marcello (Primerjalna književnost, 2019)
This article is a case study showing two examples of literary relations between Canada and the United States of America. Proceeding from a historical overview of the Canadian geopolitical situation and the situation in the publishing market in the 19th and 20th centuries, the paper defines the basis of the newly established national ideology as shown in the poetry of the so-called Confederation poets. The basis of their ideas is no doubt British-Canadian cultural nationalism, but the paper focuses on the poetry of Archibald Lampman in order to show the dependence of their late-19th-century literary idiom on both American ideas and the American literary market. In the topos of nature - specifically in the images of menacing nature, the 'northern frontier' etc. -, the binarism between the American source and its Canadian modification also becomes inscribed in the Canadian national imaginary. The most influential imagery of the standard Canadian national myth was explicated by Northrop Frye and Margaret Atwood during the second wave of Canadian nationalism in the 1960s. Nevertheless, during the second wave of nationalism, the denial of the continental binarism was at its peak. The reaction of nationalist circles to the presentation of the Governor General%s Award to George Bowering shows their explicit rebuttal of contemporary American poetry personified in the winner of the Award, despite the fact that Allen Ginsberg's poems and Charles Olson's theory of projective verse can be seen as co-shaping the poetry of several Canadian nationalist poets of the time.
Keywords: Acorn, Milton; Atwood, Margaret; Innis, Harold; kanadska književnost; konfederacijski pesniki; kulturna identiteta; Lampman, Archibald; literarni nacionalizem; odnos do Amerike